Tau as a potential therapeutic target for ischemic stroke - Chen, Xin (Aging (Albany NY), 2019)
Tau is a protein mainly expressed in adult human brain. It plays important roles both in neurodegenerative diseases and stroke. Stroke is an important cause of adult death and disability, ischemic stroke almost account for 80% in all cases. Abundant studies have proven that the increase of dysfunctional tau may act as a vital factor in pathological changes after ischemic stroke. However, the relationship between tau and ischemic stroke remains ununified. Based on present studies, we firstly introduced the structure and biological function of tau protein. Secondly, we summarized the potential regulatory mechanisms of tau protein in the process of ischemic stroke. Thirdly, we discussed about the findings in therapeutic researches of ischemic stroke. This review may be helpful in implementing new therapies for ischemic stroke and may be beneficial for the clinical and experimental studies.